2020
DOI: 10.1094/mpmi-07-19-0197-a
|View full text |Cite
|
Sign up to set email alerts
|

The Genome Sequence of Five Genotypes ofFusarium oxysporumf. sp.vasinfectum: A Resource for Studies on Fusarium Wilt of Cotton

Abstract: Fusarium oxysporum f. sp. vasinfectum is an important plant pathogen responsible for vascular wilt disease on cotton. Members of this group are known to carry supernumerary chromosomes that encode virulence factors. We sequenced the genomes of five F. oxysporum f. sp. vasinfectum isolates, including the genome of a representative of the highly virulent genotype race 4, at a high coverage to assemble reference-quality genomes. These genomes provide a necessary resource for comparative genomic analyses to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The trimmed reads from samples of Fov ‐infected Fov7 _KO#5 hypocotyls and in vitro‐grown Fov were mapped to the genome of Fov race 4. [ 28 ] It was found that 0.08–0.68% of the total reads derived from Fov at 5–10 dpi, yielding uniquely aligned read counts from 20799 to 236807 (Table S6, Supporting Information). The varied fungal mRNA reads over the time course revealed hyphal proliferation within host xylem vessels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trimmed reads from samples of Fov ‐infected Fov7 _KO#5 hypocotyls and in vitro‐grown Fov were mapped to the genome of Fov race 4. [ 28 ] It was found that 0.08–0.68% of the total reads derived from Fov at 5–10 dpi, yielding uniquely aligned read counts from 20799 to 236807 (Table S6, Supporting Information). The varied fungal mRNA reads over the time course revealed hyphal proliferation within host xylem vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Raw reads were trimmed by fastp to get clean reads. [ 73 ] The trimmed reads of J668 and Fov7 _KO#5 were uniquely mapped to the TM‐1 genome [ 74 ] with HISAT2 [ 75 ] using the –dta option, the trimmed reads of Fov7 _KO#5 were also uniquely mapped to the Fov race 4 genome [ 28 ] with Fov spores cultured in vitro as control. Since lacking of gene prediction and annotation of Fov race 4 genome, MAKER pipeline [ 76 ] was used to predict protein‐coding genes of Fov race 4, protein domains and Gene Ontology (GO) terms for each gene were annotated using InterProScan.…”
Section: Methodsmentioning
confidence: 99%
“…Plant pathogenic fusaria have been assessed for interspecific genetic variation to identify genomic features important for plant host infection [ 1 , 2 ]. In addition, intraspecific genetic variation is a powerful tool to identify potential mechanisms for disease development by pathogenic fungi [ 31 , 32 ]. This study presents a whole genome comparison between two F. oxysporum isolates collected from koa roots, one pathogenic ( Fo koae 44) and one non-pathogenic ( Fo 170) isolates.…”
Section: Discussionmentioning
confidence: 99%
“…We downloaded 490 nucleotide assemblies of FOSC publicly available on GenBank (including genomes from these studies: Ma et al 2010 , Thatcher et al 2012 , Guo et al 2014 , Kitts et al 2016 , Pu et al 2016 , van Dam et al 2016 , Williams et al 2016 , Singh et al 2017 , van Dam & Rep 2017 , Armitage et al 2018 , Ayhan et al 2018 , Lv et al 2018 , Urbaniak et al 2018 , Asai et al 2019 , Gebru et al 2019 , Henry et al 2019 , Seo et al 2019 , Taylor et al 2019 , Urbaniak et al 2019 , Achari et al 2020 , Batson et al 2020 , Fokkens et al 2020 , Henry et al 2020 , Hudson et al 2020 , Kanapin et al 2020 , Khayi et al 2020 , Kim et al 2020 , Krasnov et al 2020 , Li et al 2020 , Srivastava et al 2020 , Thangavelu et al 2020 , Wang et al 2020 , Yu et al 2020 , Zhang et al 2020 , Henry et al 2021 , Chang & Cook unpublished). Genes were predicted in Augustus using a model of F. graminearum ( Stanke & Morgenstern 2005 ).…”
Section: Methodsmentioning
confidence: 99%